AB0100 The Role of Delta/Notch like Egf-Related Receptor in Chondrogenesis of Human Mesenchymal Stem Cells. (10th June 2014) - Berninger, L.; Balkenhol, A.; Müller-Ladner, U.; Neumann, E.; Geyer, M.
Abstract : Background: The Delta/Notch like EGF-related receptor (DNER) is a single-pass transmembrane protein with characteristic EGF-like repeats in the extracellular domain, similar to those of the Notch receptor and its ligand Delta. DNER is an activator of the Notch signaling pathway, which plays a major role in cell fate determination and differentiation. In our previous study, an overexpression of DNER was observed in lesional areas of human osteoarthritic articular cartilage when compared to unaffected zones of the same tissue. Objectives: Based on these findings we analyzed the role of DNER in the chondrogenic differentiation of human mesenchymal stem cells (hMSC). Methods: HMSCs were nucleofected with an overexpression vector for DNER and a control vector. Chondrogenic differentiation of the hMSCs was performed in a pellet mass culture system for 28 days. The culture medium was supplemented with transforming growth factor beta 3 (TGF-β3) and dexamethasone. Overexpression of DNER and the effect on specific chondrogenic markers like aggrecan, collagen type 1 and 2, Sox9, collagen type 10 were analyzed with immunohistochemical staining and semi-quantitative real-time PCR. Chondrogenesis of the hMSCs was monitored using alcian blue staining. Results: Alcian blue staining increased over time assuming chondrogenic differentiation of the hMSCs. Histologically, an overexpression of DNER was detected 7 days after nucleofection and remained stable during chondrogenesis, whereas no staining of DNER could be detected in the mock-transfected cells (ctr cells). Collagen 1 expression was higher in the ctr cells at the beginning of chondrogenesis compared to the pDNER-nucleofected cells (pDNER cells) and decreased in both over time. Collagen 2 was slightly expressed from day 21 in the ctr and pDNER cells. Sox9 was greater expressed in the ctr cells at the beginning of chondrogenesis and decreased in a time-dependent manner. In pDNER cells the Sox9 expression increased at day 14 and remained stable over time. The collagen 10 level is constantly higher in the pDNER nucleofected cells compared to the ctr cells. In both, the expression increased in a time-dependent manner. Aggrecan expression increased during chondrogenesis in the ctr and pDNER cells but the expression was higher in the pDNER nucleofected cells on day 28. The semi-quantitative real-time PCR data confirmed the overexpression of DNER 2 days after nucleofection and the effect, that collagen 1 expression is downregulated and collagen 2 expression upregulated in the pDNER transfected cells compared to control until day 14. Conclusions: Since DNER overexpression led to a downregulation of collagen type 1 in the hMSCs, while the expression of collagen type 2 and aggrecan were upregulated, our results support the idea that DNER might positively influence chondrogenesis and exert a reparative role during OA pathophysiology. This promotion might be regulated via an intermediate overexpression of collagen type 10. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5616